Analisis Komposisi Asam Lemak dari Mikroalga Laut Navicula salinicola - Ramdanawati, Liska; Kurnia, Dewi; Kusumaning Tyas, Vita Aji; Nurachman, Zeily (Al-Kimia, 2018)
Indonesia is an aquatic country with potential biodiversity. One of the potential biodiversity is microalgae. Microalgae potential to be developed as a functional food with the characteristics of its fatty acids. The most fatty acids found in diatoms are myristic acid, palmitic acid, DHA and EPA. One of marine microalgae contain lot of fatty acids is diatom Navicula salinicola. This study was aim to analyze fatty acid composition of marine microalgae Navicula salinicola. Navicula salinicola was cultivated in Guillard medium with 2.5; 5; and 7.5 % of nitrogen composition and cultivated for 11 days. Dry biomass obtained from harvesting was used for the extraction. Extraction of lipid from microalgae used Bligh & Dyer method with 9,9%; 14.5%, and 17.5% of oil yield. Result of GC-FID analysis that were 6 types of fatty acids that identified are palmitic acid, myristic acid, pentadecanoic acid, stearic acid, palmitoleic acid and eicosapentanoic acid, EPA. The highest fatty acid was palmitic acid with fatty acids percentage were 64.04%; 65.03%; and 53.55% respectively.